2001
DOI: 10.1161/01.cir.103.10.1428
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Cardiac Rhythm Relationships With Bisoprolol Benefit in Chronic Heart Failure in CIBIS II Trial

Abstract: on behalf of the CIBIS II InvestigatorsBackground-␤-Blockade-induced benefit in heart failure (HF) could be related to baseline heart rate and treatmentinduced heart rate reduction, but no such relationships have been demonstrated. Methods and Results-In CIBIS II, we studied the relationships between baseline heart rate (BHR), heart rate changes at 2 months (HRC), nature of cardiac rhythm (sinus rhythm or atrial fibrillation), and outcomes (mortality and hospitalization for HF). Multivariate analysis of CIBIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
158
1
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 452 publications
(170 citation statements)
references
References 12 publications
(2 reference statements)
5
158
1
6
Order By: Relevance
“…The evidence from RCTs indicates that β-blockers can be used safely and successfully in most elderly patients with CHF. [5,12,25] Further evidence comes from the SENIORS trial which was specifically designed to investigate the effects of beta-blockade (Nebivolol) in elderly CHF patients (mean age 76 years). [7] Bradycardia was reported as an adverse event in 118/1067 (11%) patients in β-blockers arm versus 28/1061 (2.6%) patients in placebo arm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The evidence from RCTs indicates that β-blockers can be used safely and successfully in most elderly patients with CHF. [5,12,25] Further evidence comes from the SENIORS trial which was specifically designed to investigate the effects of beta-blockade (Nebivolol) in elderly CHF patients (mean age 76 years). [7] Bradycardia was reported as an adverse event in 118/1067 (11%) patients in β-blockers arm versus 28/1061 (2.6%) patients in placebo arm.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6,9,10] These results should alleviate concerns in prescribing β-blockers particularly in patients with heart failure where the absolute survival benefits of β-blockers are most pronounced. [11,25] However, medication could be a double-edge sword.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One hypothesis suggests that amiodarone can induce atrioventricular delay, especially in patients with severe left ventricular failure (ejection fraction <30%). 33,34 Dronedarone, a new derivative of amiodarone, was reported to be associated with an increase in mortality in patients with chronic heart failure. 15,16,35 Our results showed that the mortality rate in those who received long-term amiodarone therapy was low (4.7 per 100 patient-years).…”
Section: Discussionmentioning
confidence: 99%